Etiology of UTI and Frequency of ESBL Producing Bacteria Isolated from Patients of Dhaka Medical College Hospital with Their Antimicrobial Susceptibility Pattern - Begum, Shahin Ara; Afreen, Shabeen; Ahamed, Farook; Chowdhury, Akhtaruzzaman; Jobayer, Mohammad; Samsuzzaman, SM (Journal of Dhaka Medical College, 2017)
Background: Urinary tract infections (UTIs) are the most common of all bacterial infections and occur at any time in the life of an individual. ESBL producing bacteria particularly Escherichia.coli is one of the most common causes of UTIs both in community and healthcare associated settings. Emergence of multidrug resistance (MDR) is quite alarming and cause failure of empirical treatment of UTIs. As a result increase the morbidity and mortality rate in the developing countries like Bangladesh. Objective: The objective of this study was to find out the bacteria causing UTI from urine culture and detection of ESBL producing Esch.coli and K.pneumoniae with their anti- microbial susceptibility pattern. Materials and Methods: A total of 1750 urine samples were collected from patients with symptoms and suspected UTI. Clean catch mid-stream urine samples were collected from indoor and outdoor patients of Dhaka Medical College Hospital during January 2015 to July 2015.Urine specimens were cultured in 5% Blood agar and MacConkeys agar media. The isolated bacteria were identified by gram staining and biochemical tests. Antimicrobial susceptibility and detection of ESBL were done by disc diffusion method. Result: Out of 1750 urine samples, 403(23.03%) were positive by culture. Among the culture positive cases, 216 (53.59%) were female and 187 (46.41%) were male. The most common isolated bacteria were Esch.coli 295(73.20%) followed by Pseudomonas aeuroginosa 85(21.09%), K.pneumoniae10(2.48%), Proteus spp. 4(.99%), Acinetobacter spp. 5(1.2%), Coagulase negative Staphylococcus (CONS) 4(.99%). Among the isolated Esch.coli and K.pneumoniae, ESBL producing bacteria were 202 (68.47%) and 5 (50%) respectively. All the isolated bacteria showed low level susceptibility to all antibiotics that are used during the study period. Conclusion: Treatment of UTIs is difficult when caused by multidrug resistant bacteria. Analysis of culture and sensitivity data should be done periodically to identify ESBL producing bacteria for proper treatment of UTIs. J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 26-31